Clinical, neurophysiological evaluation and genetic features of axonal Charcot–Marie–Tooth disease in a Chinese family - Cao, Li; Yang, Jie; Zhang, Xiaohuan; Wang, Xu; Chen, Zhangyuwei; Tan, Song; Yang, Jiyun (Frontiers in Neurology, 2024)
Charcot–Marie–Tooth disease (CMT) is a group of inherited peripheral neuropathies related to variants in the mitochondrial transfer RNA (mt-tRNAval) gene. Here, we report a Chinese family harboring the m.1661A>G variant in the mt-tRNAval gene. Clinical evaluation, neuroelectrodiagnostic testing, and nerve biopsy were performed on four affected family members. Weakness, spasms, and pain in the limbs (especially in the lower limbs) were the main complaints of the proband. Physical examination revealed atrophy and weakness in the distal limbs, increased muscle tone, and hyperreflexia in four limbs. Neuroelectrodiagnostic tests and nerve biopsy supported an axonal polyneuropathy. This study furthers the understanding of phenotype diversity caused by variants in the mt-tRNAval gene in CMT.